2012
DOI: 10.1590/s1516-80342012000300004
|View full text |Cite
|
Sign up to set email alerts
|

Conforto acústico na percepção de escolares alfabetizados

Abstract: OBJETIVO: Verificar o conforto acústico de alunos alfabetizados. MÉTODOS: Participaram da pesquisa 82 crianças, de 8 a 10 anos, alunos do terceiro e do quarto ano do Ensino Fundamental, de quatro escolas municipais de Santa Maria. Dividiu-se a amostra em dois grupos - expostos e não expostos a níveis maiores que 80 dB(A). Para a seleção da amostra realizou-se inspeção visual do meato acústico externo, audiometria tonal e vocal e timpanometria. Para a pesquisa do conforto acústico foi aplicado um questionário b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 14 publications
0
13
0
3
Order By: Relevance
“…When the students were asked to evaluate the interference of noise in the teaching-learning process, the majority pointed out that they were able to hear the teacher's voice, but were unable to understand, and a high percentage reported that it was C4 1 10 9 90 3 30 7 70 0 0 10 100 C5 3 30 7 70 3 30 7 70 0 0 10 100 C6 2 20 8 80 4 40 6 60 0 0 10 100 C7 0 0 10 100 3 30 7 70 2 20 8 80 C8 2 20 8 80 4 40 6 60 1 10 9 90 C9 0 0 10 100 0 0 8 100 1 10 9 90 C10 3 30 7 70 5 50 5 50 0 0 10 100 Total 12 12 88 88 34 34 64 64 4 4 96 96 Fisher's Exact Test (p≤0,05) OBS: some columns do not add up to 100% since answers "I don't know" were not included in the table harmful to their learning or to their grades (23) . Noise, due to its frequency and intensity does not allow the teacher's speech to be fully head and, as a consequence, requires the student to make an extra effort and concentrate in order to separate the teacher's voice from background noise and apprehend meaning from what is being said (8,9,14) .…”
Section: Discussionmentioning
confidence: 99%
“…When the students were asked to evaluate the interference of noise in the teaching-learning process, the majority pointed out that they were able to hear the teacher's voice, but were unable to understand, and a high percentage reported that it was C4 1 10 9 90 3 30 7 70 0 0 10 100 C5 3 30 7 70 3 30 7 70 0 0 10 100 C6 2 20 8 80 4 40 6 60 0 0 10 100 C7 0 0 10 100 3 30 7 70 2 20 8 80 C8 2 20 8 80 4 40 6 60 1 10 9 90 C9 0 0 10 100 0 0 8 100 1 10 9 90 C10 3 30 7 70 5 50 5 50 0 0 10 100 Total 12 12 88 88 34 34 64 64 4 4 96 96 Fisher's Exact Test (p≤0,05) OBS: some columns do not add up to 100% since answers "I don't know" were not included in the table harmful to their learning or to their grades (23) . Noise, due to its frequency and intensity does not allow the teacher's speech to be fully head and, as a consequence, requires the student to make an extra effort and concentrate in order to separate the teacher's voice from background noise and apprehend meaning from what is being said (8,9,14) .…”
Section: Discussionmentioning
confidence: 99%
“…Equivalent sound pressure levels were elevated even in unoccupied classrooms. These facts point to inadequate planning regarding the acoustic comfort of classrooms 2,19 . The design of school buildings should prioritize adequate school acoustics, as prolonged exposure to noise can be harmful to health and have a negative impact on teaching and learning 2,8,23 .…”
Section: Resultsmentioning
confidence: 99%
“…Considering that the literature reports 65 dB as the vocal intensity of teachers in that setting 18,19 , the test was recorded and played back at 65dB. There are reports in the literature indicating that higher levels of vocal production cause symptoms of vocal fatigue, a burning sensation in the throat, vocal strain, and, over time, laryngeal alterations 8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these sources of sound pollution, the teaching-learning activity itself is also related to the production of noise (3) . The presence of noise in classrooms is an important distractor (3,4) and may interfere negatively in the academic activities, which demand great concentration and attentive listening to the professor's speech (1,2,4,5) .…”
Section: Introductionmentioning
confidence: 99%